Faculty perspectives on generative artificial intelligence: insights into awareness, benefits, concerns, and uses - Almisad, Budour; Aleidan, Ayda (Frontiers in Education, 2025)
BackgroundThe study examined university faculty members’ perspectives on Generative Artificial Intelligence (GenAI) tools, focusing on their awareness, perceived benefits, concerns, and uses and applications in education.MethodsThe study employed a cross-sectional descriptive research design in which data were collected using a questionnaire instrument in the summer semester of the 2023/2024 academic year. The number of participants was 102 Kuwaiti faculty members.ResultsThe results showed that participant had a moderate awareness of GenAI tools, with some key areas standing out, i.e., their impact on education, ethical implications, and ease of use. Faculty members had positive and high perceptions of the benefits of GenAI tools and their applications in education, particularly in reducing administrative tasks, supporting research, fostering innovation in curriculum design, and enhancing online learning. In addition, results showed that faculty members had a moderate concern regarding GenAI and their application in education. The key problems were related to the contrary effect of GenAI on academic integrity, the potential for plagiarism, over-reliance on these tools, over-dependence on technology, and ethical implications. The participants reported moderate but lower utilization of GenAI tools than their awareness and perceptions. The results revealed significant gender-based differences in participants’ awareness, perceived benefits, and utilization of GenAI tools. In contrast, no significant variations were found in faculty members’ awareness, perceived benefits, concerns, and utilization levels based on academic rank.ConclusionBased on the findings, the study recommended providing professional development programs for faculty members and students and issuing guidelines and policies to ensure the efficient and ethical use of GenAI tools for educational purposes.